Exploring Intention in Using Quick Response Code Indonesian Standard: Technology Acceptance Model Approach - Hartutik Hartutik; Dwi Nita Aryani; R. Melda Maesarach; Rosnia Masruki; Ahmad Fauzan (Jurnal Organisasi dan Manajemen, 2024)
Purpose - This research examines the influence of people's intention to use QRIS by taking variables from the Technology Acceptance Model (TAM), namely perceived usefulness, perceived ease of use, perceived trust, attitude towards usage of QRIS and behavioral intention to use QRIS. Methodology - This research method uses a quantitative approach with a sampling technique chosen through purposive sampling. Data collection was carried out by distributing questionnaires to QRIS users. Data analysis employed SmartPLS version 4 with a sample size of 100 respondents. Findings - The results show a positive relationship but not a significant effect between perceived usefulness and perceived ease of use on behavioral intention to use QRIS. Meanwhile, perceived trust and attitude towards usage of QRIS exhibited a positive relationship and had a significant effect. Originality – Trust is an influential variable and plays a significant role in using a technology such as QRIS.